A Current Review of the Children and Young People’s Improving Access to Psychological Therapies (CYP IAPT) Program: Perspectives on Developing an Accessible Workforce - Ludlow C; Hurn R; Lansdell S (Dove Medical Press, 2020)
Chris Ludlow, 1 Russell Hurn, 2 Stuart Lansdell 1 1Child Wellbeing Practitioner Program (CYP IAPT), Postgraduate Studies Department, Anna Freud Centre, London, UK; 2CYP IAPT Therapy Program, Postgraduate Studies Department, Anna Freud Centre, London, UKCorrespondence: Chris LudlowChild Wellbeing Practitioner Program (CYP IAPT), Anna Freud Centre, The Kantor Centre of Excellence, 4-8 Rodney Street, London N1 9JH, UKTel +44 20 7794 2313Email c.ludlow@ucl.ac.ukAbstract: The CYP IAPT program has played a leading role in workforce development in the Child and Adolescent Mental Health Service (CAMHS) in England since its inception in 2011. Despite promising evidence of CYP IAPT’s benefits, significant wait times for CAHMS have convinced policy makers that a new direction for CYP IAPT is required. Since 2017, the CYP IAPT program has changed its aim from workforce development to workforce expansion, with the project aiming to train 1700 new psychological practitioners by 2021. The CYP IAPT program now consists of three training streams (a) a low-intensity workforce, (b) a schools-based workforce, and (c) a high-intensity workforce based on the original CYP IAPT curriculum. The purpose of this paper is to outline the three CYP IAPT workforce streams. As will be reviewed, changes to CYP IAPT have occurred within the context of emerging ideas from dissemination science and government reviews that outline the shortcomings of traditional service models. Consequently, CYP IAPT practitioners are now increasingly being trained in the delivery of novel psychological interventions to address some of these shortcomings. A range of low-intensity interventions are being deployed by CYP IAPT practitioners to target mild-to-moderate anxiety, depression, and conduct. A recent meta-analysis indicates that low-intensity psychological interventions show promise for children and adolescents in efficacy trials. Nevertheless, further research is required to understand its effectiveness in real-world settings and to see if treatment effects are sustained over time. As such, this paper recommends that CYP IAPT services evaluate the long-term effectiveness of low-intensity work and subject their methods and findings to peer review.Keywords: psychological therapies, dissemination, mental health disorders, child/adolescent, guided self-help, cognitive behavior therapy